2015
DOI: 10.4236/aid.2015.54023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Malaria Control Program on the Prevalence of Malaria, Fever and Anaemia in Children under Five Years in the Hohoe Municipality of Ghana: A Comparative Analysis of Cross-Sectional Surveys

Abstract: Background: Malaria and anaemia continue to adversely impact the health of children in Ghana. Hohoe is an area of intense and prolonged, seasonal malaria transmission. In 2006, malaria control programme activities which provided Insecticide Treated Bed-Nets (ITNs) to resident children under five years and Artemisinin Combination Therapies (ACTs) for the management of malaria were introduced into the Hohoe Municipality. Before the introduction of the control programme, baseline surveys were carried out in commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…The sample size was estimated on the basis of the following: 95% confidence level (Z) and power of 80%, the prevalence (P) of malaria in children aged less than 5 years in November 2010 (end of rainy season) as 33.3% [10]. The least acceptable prevalence of malaria was 5.0%.…”
Section: Sampling and Sample Size Determinationmentioning
confidence: 99%
“…The sample size was estimated on the basis of the following: 95% confidence level (Z) and power of 80%, the prevalence (P) of malaria in children aged less than 5 years in November 2010 (end of rainy season) as 33.3% [10]. The least acceptable prevalence of malaria was 5.0%.…”
Section: Sampling and Sample Size Determinationmentioning
confidence: 99%
“…Ahead of implementing the intervention, baseline surveys were carried out in June and November 2006 [22]. Follow up surveys were carried out in 2010 and 2015 to assess the influence of the intervention of LLINs, IPTs and ACTs use, as well as changes in malaria incidence and prevalence in the Municipality.…”
Section: Advances In Infectious Diseasesmentioning
confidence: 99%
“…The number of malaria infection was observed to increase during harmattan and the months of the rainy season, especially in August and September, notwithstanding a decline in the prevalence of malaria among children under-five [16]. Findings from studies in Ejisu-Juaben and Hohoe, Ghana, reported that the prevalence of malaria and anaemia was significantly higher during the pre-rainy season than the post-rainy season [19,20]. The autors elaborated that rainfall increases the possible breading grounds for mosquito larvae, eventually resulting in more vectors to spread the disease during pre-rainy season.…”
Section: Introductionmentioning
confidence: 99%